1968
DOI: 10.1002/cne.901340404
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar cortex of rat and other animals. A structural and ultrastructural study

Abstract: Cerebellar cortex was studied in 100 rats and other animals, 15-30 days old, using Golgi, intravitam methylene blue, and ultrastructural methods. Marchi and Nauta provided certain controls. Degeneration of afferent terminals was sought following lesions of pons and olive.In normal material, emphasis was upon the chanqing field relations between folial summit, side wall, and sulcus. Many previous findings of Fox, Ramon y Cajal and Snider were confirmed, and the effort made to reconcile departures from character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In the present study, no CR-positive Lugaro cells were found. Lugaro cells have been found in all mammalian species studied (Fox, 1959;O'Leary et al, 1968;Palay and Chan-Palay, 1974;Braak and Braak, 1983;Laine and Axelrad, 1996). Assuming that these cells are also present in the cetaceans presently studied, one may suggest that they are CR-negative.…”
Section: Discussionmentioning
confidence: 91%
“…In the present study, no CR-positive Lugaro cells were found. Lugaro cells have been found in all mammalian species studied (Fox, 1959;O'Leary et al, 1968;Palay and Chan-Palay, 1974;Braak and Braak, 1983;Laine and Axelrad, 1996). Assuming that these cells are also present in the cetaceans presently studied, one may suggest that they are CR-negative.…”
Section: Discussionmentioning
confidence: 91%
“…Histologically, cerebellar cortex exhibits a generally trilaminate architecture, which is similar in birds and mammals (Ramón y Cajal, 1909, 1911; Iwaniuk et al, 2006; Sultan and Glickstein, 2007). Whereas limited aspects of cerebellar neuron morphology have been described in some vertebrate species (e.g., mormyrid electric fish: Han et al, 2006; teleost fish: Murakami and Morita, 1987; alligator: Nicholson and Llinas, 1971; cat: Melik-Musyan and Fanardzhyan, 2004; duck: O'Leary et al, 1968; dolphin: Adanina, 1965; rhesus monkey: Fox et al, 1967; Rakic, 1972; human: Braak and Braak, 1983), the most detailed research has focused on rodents. In particular, Palay and Chan-Palay (1974) provided a comprehensive examination of the cerebellar cortex of the rat, documenting organizational features, neuronal morphology, and ultrastructure at the electron microscopic level.…”
Section: Introductionmentioning
confidence: 99%
“…Light and transmission electron microscopic studies of vertebrate cerebellar cortex (Carrea et al 1947;ChanPalay andPalay 1970, 1971;Fox et al 1969;Szentagothai 1966, 1980;Ito 1984;Larramendi and Victor 1967;Murphy et al 1973;O'Leary et al 1968O'Leary et al , 1971Palay and Chan-Palay 1974;Rivera-Domínguez et al 1974;Scheibel and Scheibel 1954;Szentagothai and Rajkovits 1959) have supported and extended the basic morphologic aspects of climbing fibers as reported more than one hundred years ago, in the pioneering and classical account of Ramón y Cajal (1888, 1955.…”
Section: Introductionmentioning
confidence: 71%